2005
DOI: 10.1097/01.tp.0000187132.49178.ec
|View full text |Cite
|
Sign up to set email alerts
|

Living Related Liver Transplantation: The Ultimate Technique to Expand the Donor Pool?

Abstract: Today, living donor liver transplantation (LDLT) is well established in many centers as a therapeutic method for end-stage liver disease. LDLT is an option for selected cases and is still under development. From the beginning of LDLT until now, many innovations have been presented and as a consequence both the surgical and medical complications in both donors and recipients reduced greatly. As a benefit, this procedure enriches the donor organ pool and reduces the imbalance between the scarcity of organ resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
9
0
2
Order By: Relevance
“…The reasons for the difference in outcomes of HCV‐infected live donor transplant recipients early in a center's experience vs. later are not completely clear. However, most transplant physicians recognize the unique technical challenges in performing living donor transplants in adults, and several publications attest to the higher rate of graft loss early in the posttransplant period related to vascular problems, biliary complications, and small‐for‐size syndrome 10, 11. These technical issues have great relevance in the first 90 days posttransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the difference in outcomes of HCV‐infected live donor transplant recipients early in a center's experience vs. later are not completely clear. However, most transplant physicians recognize the unique technical challenges in performing living donor transplants in adults, and several publications attest to the higher rate of graft loss early in the posttransplant period related to vascular problems, biliary complications, and small‐for‐size syndrome 10, 11. These technical issues have great relevance in the first 90 days posttransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Complicating factors including the activation of the innate immune response are often present in the regenerating organs, although their effects on the overall outcome of tissue regeneration are not well understood. The current series of studies has focused on the effects of T cell-mediated liver injury during the regenerative response.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Saidi et al reported that recipients of leftlobe LDLT had a greater mean duration of stay (24.9 days vs. 18.2 days), higher re-transplantation rates (20.3% vs. 10.9%), lower allograft survival, and inferior survival compared with recipients of DDLT [76]. LDLT should be carefully considered because donor morbidity and mortality still exist, and problems such as matching the graft size with the recipient area and postoperative complications cannot be avoided [77].…”
Section: Liver Transplantationmentioning
confidence: 99%